Structural investigation of C6/36 and Vero cell cultures infected with a Brazilian Zika virus. - Debora Ferreira Barreto-Vieira; Fernanda Cunha Jácome; Marcos Alexandre Nunes da Silva; Gabriela Cardoso Caldas; Ana Maria Bispo de Filippis; Patrícia Carvalho de Sequeira; Elen Mello de Souza; Audrien Alves Andrade; Pedro Paulo de Abreu Manso; Gisela Freitas Trindade; Sheila Maria Barbosa Lima; Ortrud Monika Barth (PLoS ONE, 2017)
Zika virus (ZIKV) is a member of the flavivirus genus, and its genome is approximately 10.8 kilobases of positive-strand RNA enclosed in a capsid and surrounded by a membrane. Studies on the replication dynamics of ZIKV are scarce, which limits the development of antiviral agents and vaccines directed against ZIKV. In this study, Aedes albopictus mosquito lineage cells (C6/36 cells) and African green monkey kidney epithelial cells (Vero cells) were inoculated with a ZIKV sample isolated from a Brazilian patient, and the infection was characterized by immunofluorescence staining, phase contrast light microscopy, transmission electron microscopy and real-time RT-PCR. The infection was observed in both cell lineages, and ZIKV particles were observed inside lysosomes, the rough endoplasmic reticulum and viroplasm-like structures. The susceptibility of C6/36 and Vero cells to ZIKV infection was demonstrated. Moreover, this study showed that part of the replicative cycle may occur within viroplasm-like structures, which has not been previously demonstrated in other flaviviruses.